Issues at the fore in the land of Magnuson and Stevens: A summary of the 14th Bevan Series on Sustainable Fisheries. (April 2015) - Kuriyama, Peter T.; Siple, Margaret C.; Hodgson, Emma E.; Phillips, Elizabeth M.; Burden, Merrick; Fluharty, David; Punt, André E.; Essington, Timothy E.; Henderschedt, John; Armstrong, David A.
Abstract: The Magnuson–Stevens Act is the United States׳ premier law governing fisheries conservation and management. Congress has revisited the Act multiple times since its inception in 1976—most recently in 1996 with the Sustainable Fisheries Act and in 2006 with the Magnuson Stevens Act—and is currently in the process of reauthorizing the Act. The University of Washington focused the 14th annual Bevan Series on Sustainable Fisheries on issues surrounding reauthorization. The symposium featured a diversity of stakeholders, including fisheries scientists, managers, policy analysts, students, non-governmental organizations, Tribes, and industry. The symposium explored the Act׳s history, means of ending overfishing and ensuring accountability, lessons from U.S. West Coast and North Pacific fisheries, and challenges and solutions to ecosystem-based fisheries management.